Ethics and communication in organisations - Brett Davidson (Communicare)
This article deals with the question of managers' ethical responsibilities in their communication with em ployees. The idea of a social contract for business is used as a starting point for the development of an ethi cal standard for communication. Fo cusing on the concept of corporate culture, the author looks at the role of power, rhetoric and ideology in exerting symbolic control in the organisation. He argues that although some believe that the presence of rhetoric and of power differences precludes the possibility of ethical communication, this is not necessar ily true. Finally, Sonja Sackmann's view of corporate culture as a dy namic construct is introduced as an approach that seems to promote ethical communication with respect to employees.